ADOPTION OF THE BASEL II ACCORD BY COMMERCIAL BANKS IN KENYA - Nkirote, Kinoti Julie; McFie, Dr. J. (Journal of Accounting, 2016)
Purpose: The focus of the study was on the possibility of adopting Basel II accord by Kenya commercial banks. Methodology: The study adopted a descriptive survey design. A population of 45 commercial banks was identified from the central bank of Kenya website. A census was undertaken as the population was small enough. A self-report questionnaire was the data collecting instrument used in this study. Consequently, a questionnaire was handed out to each bank bringing the total number of questionnaires to 45. A nonrandom sampling/purposive sampling technique was used and managers in risk management, audit, operations and finance were highly preferred respondents. Results: The study findings indicated that that the majority of banks had not complied with the prerequisites to Basel II. In addition, the study identified the challenges to implementation of Basel II prerequisites as lack of expertise, poor regulation and supervision and lack of credit information. Unique contribution to theory, practice and policy: The study recommended that the challenges identified can be addressed if a collaborative effort between banks and the central bank of Kenya was used to impart knowledge on the implementation of Basel II and its prerequisites. A credit reference bureau would also be very effective in availing credit information for the various banks assets. The area of further study identified in the study relates to the empirical relationship between the costs of implementing Basel II and the financial performance of banks